Safe Danger – On the Experience of Challenge, Adventure and Risk in Education. Issue 1 (2nd January 2017) - Martínková, Irena; Parry, Jim
Abstract: This article reconsiders the presence and value of danger in outdoor and adventurous activities and sports in safety-conscious societies, especially in relation to the education of children and youth. Based on an original analysis of the relation between the concepts of 'risk' and 'danger', we offer an account of the relation between challenge, adventure, risk and danger, and emphasise the importance of teaching risk recognition, risk assessment, risk management and risk avoidance to children and youth, without the necessity of exposing them to jeopardy in dangerous situations. Our conclusion is that 'Safe Danger' describes what educators should seek, namely: the educational benefits of the challenges set by risk-taking and the demands of risk-facing, including those in adventurous situations, which are obtainable in the absence of significant danger, and which contribute to risk education. The educational value of adventurous and outdoor pursuits lies elsewhere than in the opportunities that they present for danger-facing, for example in their promotion of self-reliance, confidence, ability to team-work, and especially in their promotion of risk education, as an integral aspect of everyday life planning, as preparation for the day's adventurous challenges, and as an instrument of task completion.